Bullous epidermolysis in newborn - Molina-Piedra, Dana (2023)
Epidemolysis bullosa is a genetic disease. Clinical picture include blistering and ulcers after friction or trauma. Skin lesions may be cutaneous or extracutaneous. Family history, clinical findings, lab tests and microscopic examination are needed to make the diagnosis of the disease. A diagnosed case is presented in this paper, it is a 25 days female baby who was assisted at the Teaching Pediatric Hospital ″Jose Luis Miranda ″in Santa Clara. Clinical findings are described in the paper, as well as, comments about different types of Epidemolysis and their clinical manifestations, since this disease is not frequent in the pediatric age.